Predictors of Operative Mortality in Cardiac Surgical Patients with Prolonged Intensive Care Unit Duration - LaPar, Damien J (2013)
BACKGROUND: Several systems have been developed to predict mortality following intensive care unit (ICU) admission in medical and surgical patients. However, a similar tool specific to cardiac surgical patients with prolonged intensive care unit duration does not exist. The purpose of the present study was to identify independent perioperative predictors of operative mortality among cardiac surgical patients with prolonged ICU duration. STUDY DESIGN: From 2003-2008, 13,105 cardiac surgical patients with ICU durations greater than 48 hours were identified within a statewide database. Perioperative factors, including Society of Thoracic Surgeons Predicted Risk of Mortality (STS PROM), were evaluated. Univariate and multivariate analyses identified significant correlates of operative mortality and their relative strength of association as determined by the Wald χ(2) statistic. RESULTS: Mean patient age was 66.8±11.2 years, median ICU duration was 76.5 [56.0-124.0] hours, and mean STS PROM was 4.4%±6.2%. Among preoperative and operative factors, intra-aortic balloon pump use, patient age, immunosuppressive therapy, hemodialysis requirement, cardiopulmonary bypass time, and heart failure proved to be the strongest correlates of mortality (all p<0.05) on risk-adjusted multivariate analysis. Interestingly, type of cardiac procedure had no significant association with mortality after risk adjustment. Among postoperative complications, cardiac arrest, prolonged mechanical ventilation (>24 hours) and stroke were the strongest predictors of risk-adjusted mortality (all p<0.001). CONCLUSIONS: Operative mortality may be predicted by select risk factors for cardiac surgical patients with prolonged intensive care unit duration. Patient age, preoperative intra-aortic balloon pump, and postoperative cardiac arrest, prolonged ventilation and stroke have the strongest association with mortality. Identification of these factors in the perioperative setting may enhance resource utilization and improve mortality following cardiac surgery.